Distal Extension Denture – Case Report and Overview [Corrigendum] - Yeung C; Leung KCM; Yu OY; Lam WYH; Wong AWY; Chu CH (Dove Medical Press, 2021)
Yeung C, Leung KCM, Yu OY, Lam WYH, Wong AWY, Chu CH. Clin Cosmet Investig Dent. 2020;12:493—503.   Details of the same case report were previously reported by the authors in Yeung C, Leung KCM, Yu OY, Lam WYH, Wong AWY, Chu CH. Prosthodontic Rehabilitation and Follow-Up Using Maxillary Complete Conventional Immediate Denture. Clin Cosmet Investig Dent. 2020;12:437–445. Figures 1-5, 11 and 12-14 on pages 494, 496 and 497, respectively, should have included the following note: Note: Copyright ©2020. Dove Medical Press. Reproduced from Yeung C, Leung KCM, Yu OY, Lam WYH, Wong AWY, Chu CH. Prosthodontic Rehabilitation and Follow-Up Using Maxillary Complete Conventional Immediate Denture. Clin Cosmet Investig Dent. 2020;12:437–445.   Read the original article